(untitled) (Islamic Sciences Journal, 2023)
Praise be to Allah who fulfilled his righteous grace, and peace be upon the final prophet with whom Allah sealed the messages, and upon his family, companions and those who followed them with goodness until the Day of Meeqat, and after: This research deals with collecting and directing the correct Qur’anic readings in (Tafsir al-Baidawi called: Anwar al-Tasul wa Asrar al-Ta’wil), the first half of Surat al-Ma’idah. I have adopted the inductive approach, by following the sayings of Imam al-Baidawi in narrating the verses in which the correct readings mentioned, collecting and directing them, The analytical method is shown in studying the verses in which the correct readings are contained, verifying them from the books of approved recitations, and directing them by relying on books of arguments, causes, language and morphology books, etc., dividing the verses in which the correct readings are mentioned into paragraphs, and figuring the verse that is being discussed.